2000
DOI: 10.1046/j.1469-8137.2000.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant–plant interactions and soil moisture might be important in determining ozone impacts on grasslands

Abstract: Ozone effects on plant species mixtures could depend on the characteristics of the species involved, their mixing ratio, or on environmental conditions. Predicting long-term effects on the dynamics of plant communities requires an understanding of the interactions involved. The present experiment was designed to determine the effects of ozone on grassland species in relation to mixing ratio and soil water content (irrigation) using binary mixtures. The grass Trisetum flavescens was grown in potted repla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…But species respond diVerently to elevated O 3 depending on speciWc O 3 uptake, mesophyll exposure, and detoxiWcation capacity (Fuhrer and Booker 2003). Thus, in plant communities, eVects on plant-plant interactions can lead to shifts in species composition (Nussbaum et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…But species respond diVerently to elevated O 3 depending on speciWc O 3 uptake, mesophyll exposure, and detoxiWcation capacity (Fuhrer and Booker 2003). Thus, in plant communities, eVects on plant-plant interactions can lead to shifts in species composition (Nussbaum et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Reduced proportions of injured leaves on O 3 exposed grasses due to the presence of a competitor have been described. For example, Trisetum flavescens responded more strongly in mixture with the low stature species Centaurea jacea than in mixture with Trifolium pratense (Nussbaum et al 2000). Similarly, Leontodon hispidus exhibited a larger increase in O 3 -induced senescence observed in the more open canopy of A. odoratum compared to the denser canopy of D. glomerata (Hayes et al 2011).…”
Section: Plant Competition and Community Compositionmentioning
confidence: 95%
“…If the total biomass of the species mixture was largely influenced by the more sensitive component, a decline in total yield of the mixture has been recorded under O 3 exposure (e.g. for Trifolium repens/Lolium perenne, Hayes et al 2009; for Trifolium pratense/Trisetum flavescens, Nussbaum et al 2000). On the other hand, a range of O 3 exposure experiments resulted in unchanged total yield quantities (e.g.…”
Section: Plant Competition and Community Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the effects of ozone on both individual grassland species and constructed communities in chamber studies have identified that a range of grassland species are sensitive to ozone and that ozone can change species composition (e.g. Ashmore and Ainsworth 1995;Nussbaum et al 2000;Rämö et al 2006, Thwaites et al 2006. Based on the sensitivity of individual species, Mills et al (2007) suggested that calcicolous and mesotrophic grasslands are among the most ozone-sensitive ecosystems in Europe.…”
Section: Introductionmentioning
confidence: 99%